Biomechanical Evaluation of the Osseointegration Levels of Implants Placed Simultaneously With Tibia, Femur, and Jaw Allogeneic Bone Grafts - Ozcan, Erhan Cahit; Sokmen, Kevser; Karasu, Necmettin; Bal, Ali; Tanrisever, Murat; Istek, Ozmen; Dundar, Serkan (Lippincott Williams & Wilkins, 2025)
In implant-supported prosthetic treatments, the jaw bones may not always have enough bone to accommodate implants. Allogeneic grafts can also be preferred as an alternative to autogenous grafts in cases of vertical and horizontal bone deficiencies. The aim of this study is to evaluate the osseointegration levels of lathe-faced titanium implants placed together with allogeneic bone tissue transplants obtained from tibia, femur, and mandible bones using a biomechanical method. Twenty-eight female Sprague Dawley rats were included in the study. The subjects were divided into groups where bone transplantations were performed together with implant placement from the tibia (n=7), femur (n=7), and lower jaw (n=7) regions. Four rats (left and right) were used as donors. Grafts, along with implants, were surgically placed in the corticocancellous part of the metaphyseal parts of the tibia bones of rats. At the end of the 2-week experimental setup, all rats were killed, and the implants and surrounding bone tissues were subjected to biomechanical reverse torque analysis (N/cm), no statistical difference was detected in terms of bone-implant fusion between the groups in which the femur and tibia bones were transplanted (P>0.05), while the bone-implant fusion value in the group in which the lower jaw bone was transplanted was found to be statistically higher than the femur and tibia bones (P<0.05). Based on the limited results of this study, it can be thought that the lower jaw allogeneic jawbone has a higher osseointegration potential than allogeneic grafts obtained from the femur and tibia.
Keywords: Allogenic bone graft; bone implant connection; femur; mandible; osseointegration; tibia